Sentinel lymph node surgery after neoadjuvant chemotherapy in patients with T2 to T4, N0 and N1 breast cancer. (October 2016) - Andreis, D.; Bonardi, S.; Allevi, G.; Aguggini, S.; Gussago, F.; Milani, M.; Strina, C.; Spada, D.; Ferrero, G.; Ungari, M.; Rocca, A.; Nanni, O.; et al.
Abstract: Background: Histological status of axillary lymph nodes is an important prognostic factor in patients receiving surgery for breast cancer (BC). Sentinel lymph node (SLN) biopsy (B) has rapidly replaced axillary lymph node dissection (ALND), and is now the standard of care for axillary staging in patients with clinically node-negative (N0) operable BC. The aim of this study is to compare pretreatment lymphoscintigraphy with a post primary systemic treatment (PST) scan in order to reduce the false-negative rates for SLNB. Methods: In this single-institution study we considered 170 consecutive T2-4 N0-1 M0 BC patients treated with anthracycline-based PST. At the time of incisional biopsy, we performed sentinel lymphatic mapping. After PST, all patients repeated lymphoscintigraphy with the same methodology. During definitive surgery we performed further sentinel lymphatic mapping, SLNB and ALND. Results: The SLN was removed in 158/170 patients giving an identification rate of 92.9% (95% confidence interval (CI) = 88.0–96.3%) and a false-negative rate of 14.0% (95% CI = 6.3–25.8%). SLNB revealed a sensitivity of 86.0% (95% CI = 74.2–93.7%), an accuracy of 94.9% (95% CI = 90.3–97.8%) and a negative predictive value of 92.7% (95% CI = 86.1–96.8%). Conclusion: Identification rate, sensitivity and accuracy are in accordance with other studies on SLNB after PST, even after clinically negative node conversion following PST. This study confirms that diagnostic biopsy and neoadjuvant chemotherapy maintain breast lymphatic drainage unaltered. Highlights: SLN biopsy is now the standard of care for axillary staging in patients with clinically node-negative operable BC. The SLN showed an identification rate of 92.9% (88.0–96.3%) and a false-negative rate of 14.0% (6.3–25.8%). SLNB sensitivity: 86.0% (74.2–93.7%), accuracy: 94.9% (90.3–97.8%) and negative predictive value: 92.7% (86.1–96.8%). This study confirms that diagnostic biopsy and neoadjuvant chemotherapy maintain breast lymphatic drainage unaltered.